Tūalakhō̜n khō̜ng chan - Kritsanā ʻAsōksin (Krung Thēp : Čhatphim læ čhatčhamnāi dōi Samnakphim Sǣng Dāo, 2011)
Descriptions of characters in the novels by the author.
In Thai.
Keywords: Thai fiction; Characters and characteristics in literature